ENVIRONMENTAL POLLUTION ASSESSMENT OF SURFACE WATER IN OMEGE COMMUNITY USING CHEMICAL DATA AND RISK-BASED EVALUATION - Temidayo E. Olagunju (Polish Journal of Natural Sciences, 2023)
Mining of mineral resources creates economic backbone for many countries but its attendant consequences on the environment and human health is far-reaching, especially when the process is done without appropriate sustainability measures. In this study, physico-chemical parameters and heavy metal load of the upstream, midstream and downstream zones of Omege River, Ebonyi State Nigeria was determined according to standard procedures. USEPA risk model was applied to estimate health risks that could be associated with five heavy metals (Zn, Fe, Cu, Pb and Cr) in the three zones of the surface water in both children and adults. EC, TDS, TSS, TS, TH, Pb and Cr were found to be above the USEPA permissible limit in the three zones of the river. CI index based on zones of the surface water was in the order of upstream < midstream < downstream while it was Zn < Cu < Fe < Cr < Pb based on the heavy metals. There was extreme high contamination by Pb in the water samples from the study area particularly in the downstream with CI reaching up 600. HQ of Pb and Cr in the three zones of the surface water was > 1 for both children and adults with that of Pb (6.64–23.57) in threatening level. HI range from 14.06 in the upstream to 3.180 in the downstream for children and from 8.71 in the upstream to 19.72 in the downstream for adults. CRI estimated for Pb and Cr were not within the acceptable limit. These results suggest potential non-carcinogenic and carcinogenic health risk in both children and adults via oral consumption of water from Omege River. Finally, this study revealed that children were at higher health risk if exposed to the heavy metals via the consumption of water from Omege River than adults.